Some Oscillation Results of Higher-Order Linear Differential Equations with Meromorphic Coefficients - Zhigang Huang (Abstract and Applied Analysis)
We investigate the growth of solutions of higher-order nonhomogeneous linear differential equations with meromorphic coefficients. We also discuss the relationship between small functions and solutions of such equations.